Evaluation of a solidary academic-pedagogical project in virtual graduate programs - Ortiz-Ordoñez, Kris Evelin; Burbano-Gonzalez, Diana Carolina; Suarez-Muñoz, Jorge Andrés (Frontiers in Education, 2025)
The consolidation of virtual education as a strategic modality in postgraduate training requires rigorous evaluations of its relevance from the student perspective. For this reason, this research aimed to compare the perceptions of students in two virtual master’s programs at the National Open and Distance University, developed under the Solidarity Pedagogical Academic Project model focused on collaboration, equity, and social commitment to strengthen learning in virtual environments. These aspects were analyzed, taking into account five key areas of this approach, namely educational resources, teaching support, assistance and guidance, pedagogical mediation, and humanistic training. The study adopted a quantitative, non-experimental, comparative cross-sectional approach. Structured surveys were applied according to the Likert scale with 25 items distributed across the areas mentioned above. To validate the statistical assumptions, tests of normality (Shapiro–Wilk), homoscedasticity (Breusch–Pagan), and independence (chi-square) were performed, determining the absence of normality, the presence of homogeneous variances, and independence between data. Based on these results, Yuen’s robust test was used to compare the medians between the groups. The results revealed that there are no statistically significant differences between the perceptions of the two groups and demonstrated the robustness and consistency of virtual learning environments, highlighting their ability to offer equitable, student-centered learning experiences aligned with high-quality standards. The effectiveness of the supportive instructional model in diverse virtual contexts is reaffirmed.